IMPLEMENTASI APLIKASI ENKRIPSI DATA: IMPLEMENTASI APLIKASI ENKRIPSI DATA MENGGUNAKAN ALGORITMA AES 128 UNTUK MENINGKATKAN KEAMANAN INFORMASI BERBASIS WEBSITE DI SMK KUSUMA BANGSA - tyastiamutiara, tyastiamutiara; Bambang Wisnu Widagdo (JUPIK : Jurnal Penelitian Ilmu komputer, 2025)
The use of web-based systems in education is increasing, including at SMK Kusuma Bangsa. The school website is used to store and manage important data such as student information, academic grades, and lesson schedules. However, weaknesses in the security system make data vulnerable to cyber attacks such as data breach and SQL injection. This research aims to implement data encryption using the AES-128 algorithm to improve information security at SMK Kusuma Bangsa. The research methods used include observation, interviews, and literature studies. The developed system was tested using the Black Box Testing method to ensure the reliability and security of data encryption. The results showed that the implementation of AES-128 is able to protect data well, prevent unauthorized access, and increase user confidence in the system. With this encryption, the risk of information leakage can be minimized, so that school data security becomes more secure.